2014
DOI: 10.1371/journal.pone.0107007
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Panel of Filovirus Sequence Capture Probes for Pathogen Detection by Next-Generation Sequencing

Abstract: A detailed understanding of the circulating pathogens in a particular geographic location aids in effectively utilizing targeted, rapid diagnostic assays, thus allowing for appropriate therapeutic and containment procedures. This is especially important in regions prevalent for highly pathogenic viruses co-circulating with other endemic pathogens such as the malaria parasite. The importance of biosurveillance is highlighted by the ongoing Ebola virus disease outbreak in West Africa. For example, a more compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…Targeted sequence capture has been used extensively to assess the human exome, as well as specific gene targets (Lovett et al 1991;Albert et al 2007;Hodges et al 2007;Okou et al 2007). Sequence capture has also been applied to the study of specific viruses (Depledge et al 2011;Duncavage et al 2011;Koehler et al 2014). Our aim was to develop a comprehensive viral targeted sequence capture panel that could be used to (1) assess all viruses known to infect vertebrate cells and (2) detect divergent viruses.…”
mentioning
confidence: 99%
“…Targeted sequence capture has been used extensively to assess the human exome, as well as specific gene targets (Lovett et al 1991;Albert et al 2007;Hodges et al 2007;Okou et al 2007). Sequence capture has also been applied to the study of specific viruses (Depledge et al 2011;Duncavage et al 2011;Koehler et al 2014). Our aim was to develop a comprehensive viral targeted sequence capture panel that could be used to (1) assess all viruses known to infect vertebrate cells and (2) detect divergent viruses.…”
mentioning
confidence: 99%
“…Diagnostic tests for BDBV infection are currently limited to various pan-filovirus reverse transcriptase-polymerase chain reaction (RT-PCR) or quantitative reverse transcriptase-PCR (qRT-PCR) protocols (Lu et al 2015) and BDBV-specific sequence capture probes for next-generation sequencing (Koehler et al 2014). A handful of BDBV-specific monoclonal or polyclonal murine, rabbit or crab-eating macaque antibodies (Ou et al 2011;Holtsberg et al 2015;Keck et al 2015;Wang et al 2015), BDBV …”
Section: Bundibugyo Virusmentioning
confidence: 99%
“…No reports on medical countermeasures against RESTV infection are available, most likely due to the perception that RESTV is not an imminent threat to humans. Diagnosis of RESTV infection is possible via pan-filovirus RT-PCR or qRT-PCR protocols (Lu et al 2015) and RESTV-specific sequence capture probes for next-generation sequencing (Koehler et al 2014). Several serological or nucleic-acid based RESTVspecific diagnostic systems have been described (Kalter et al 1995;Ksiazek et al 1999;Niikura et al 2001;Ikegami et al 2002bIkegami et al , 2003aOu et al 2011).…”
Section: Reston Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Koehler et al reported on a panel of Filovirus capture probes used in conjunction with MiSeq sequencing to enable detection of Ebola and Marburg viruses. Their method utilized DxSeq™ probes, which are singlestranded DNA probes of which both ends bind to target sequences followed by filling in of the intervening captured sequence by polymerase and subsequent circularization (Koehler et al, 2014;McCarthy, 2011). Despite the fact that a pre-amplification step was performed prior to sequence capture and subsequent MiSeq sequencing, real-time PCR was still more sensitive for detection than sequencing in this case.…”
Section: Improving the Sensitivity Of Detection Of Pathogens By Ngsmentioning
confidence: 99%